Avaliação da validade do Global Trigger Tool do Institute for Healthcare Improvement para identificação de eventos adversos em pacientes adultos hospitalizados - Sara Monteiro de Moraes (2022)
Patient safety is a fundamental principle of care and a critical component of quality healthcare. Its improvement depends on the ability to understand the frequency of occurrence and types of adverse events, in order to prioritize improvement actions. For this purpose, valid, reproducible and cost-effective measurement strategies are needed. The Global Trigger Tool (GTT) of the Institute for Healthcare Improvement (IHI) is a tool that proposes the estimation of the occurrence of adverse events through a simple, inexpensive and easy-to-execute method. It has been used in recent years as a measurement strategy in patient safety by several institutions and some national programs. Although the greater ability of the GTT to identify adverse events compared to other methods has already been demonstrated, there are few data on its accuracy. Furthermore, studies suggest that the minor harm AEs are more difficult to be identified by the GTT and that the exclusion of these events could increase the validity of the method. Objectives To assess the validity of the GTT for identifying adverse events in adult hospitalized patients for all adverse events and for the subgroup of adverse events with greater harm to the patient. Methods This is a diagnostic test study, in which the GTT is the index test and the identification of adverse events represents the condition of interest. Due to the inexistence of a gold standard test, a composite reference standard method was constructed combining the collection of information during hospitalizations and retrospective administrative and clinical data analysis for AEs identification. Both tests were applied to a random sample of 211 hospitalizations of adult patients, occurred in Oct/Nov 2016 at a large public hospital in Belo Horizonte, Brazil. The validity of the GTT was evaluated using weighted Kappa coefficient and classical measures of accuracy – sensitivity, specificity and global accuracy. The classification of adverse events in terms of severity of harm was based on the National Coordinating Council for Medication Error Reporting and Prevention (NCC MERP) Index for Categorizing Errors adapted by the IHI, with less severe events classified as “E” and those with greater severity gravity as “F-I”. Results A total of 176 adverse events were identified in 67 admissions using the reference standard method and 129 adverse events in 76 admissions using the GTT, resulting in rates of 126 and 93 adverse events /1,000 patient-days, respectively. There was substantial agreement between the methods for identification of admissions with adverse event (K=0.61; 95% confidence interval [CI] 0.49 to 0.71), and slight agreement for identification of each adverse event (K=0.09; 95%CI 0.02 to 0.19). Considering the subgroup of adverse events of greater harm (F-I), there was substantial agreement between the methods, with K=0.80 (95% CI 0.70 to 0.88) for identification of admissions with adverse event and K=0.74 (95% CI 0.64 to 0.83) for identification of each adverse event. The sensitivity, specificity and global accuracy data of the GTT for the identification of individual adverse events were, respectively, 0.41 (95% CI 0.34;0.49), 0.68 (95% CI 0, 60;0.74) and 0.54 (95% CI 0.49;0.60) for all adverse events, regardless of the harm categorization, and 0.85 (95% CI 0.72;0.93), 0.88 (95% CI 0.82;0.92) and 0.87 (95% CI 0.82;0.91) for the subgroup of adverse events categorized as harm F-I. Among the adverse events lost by the GTT are mainly adverse events related to nursing care, such as those related to peripheral venous access and gastric/enteric catheters. Conclusion The GTT proved to be a valid method for identifying adverse events in hospitalized adult patients. Its accuracy increases when minor harm AEs are not counted. Among the main adverse events missed by the GTT are those related to nursing care. Therefore, the GTT should be used in conjunction with other measurement strategies to achieve results that are representative of the quality of care provided and, thus, guide the best improvement strategies.